Beyond the Classroom: Strategic Principal Leadership in Planning Character-Based Co-Curricular Programs - Ananda Vian Saleh Presiden; Senowarsito Senowarsito; Ngurah Ayu Nyoman Murniati (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyze principal leadership in planning co-curricular programs to strengthen character education. This research used a qualitative approach with a case study design. Data were collected through semi-structured interviews, participant observation, and document analysis involving principals, vice principals, teachers, program coordinators, and relevant stakeholders. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, with data validity strengthened through triangulation and member checking. The results revealed five key practices of principal leadership in co-curricular program planning: comprehensive needs analysis, alignment of character education goals with the school's vision and mission, stakeholder engagement through collaborative planning, integration of academic learning with character development, and strategies for overcoming challenges through resource optimization and coordination. This study concluded that effective principal leadership in the planning stage is a strategic factor in the sustainability of character education through co-curricular programs. The research findings provide practical implications for strengthening the role of principals in designing contextual, collaborative, and sustainable co-curricular programs.